Brommethan [MAK Value Documentation in German language, 2016]. Issue 2 (27th April 2016) - Hartwig, A.
Methyl bromide: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated the developmental toxicity of methyl bromide. Available unpublished study reports and publications are described in detail. The maximum concentration at the workplace (MAK value) of methyl bromide is 1 ml/m 3, based on the irritant effect on the upper respiratory tract. NOAECs for prenatal developmental toxicity in rats and rabbits were 70 ml/m 3 and 40 ml/m 3, respectively. NOAELs of 30 and 10 mg/kg bw and day in rats and rabbits, respectively, were obtained in gavage studies, corresponding to 14 and 8 ml/m 3 after scaling to a concentration at the workplace. Thus, there is an adequate margin between NOAEC/L for developmental toxicity and the MAK value. However, methyl bromide is a neurotoxin and no data on developmental neurotoxicity exist. In adult mice and rats, neurotoxic symptoms like convulsions and paralysis of the hind limbs are observed. In a two‐generation study the adult F0 and F1 generations do not show such neurotoxic effects at 90 ml/m 3, which would particularly have been expected in the F1‐animals having a longer exposure time which included complete gestation. It can be inferred that offspring are not more sensitive to the neurotoxicity of methyl bromide than adults. Thus, damage to the embryo or foetus is unlikely when the MAK value is observed and methyl bromide is re‐assigned to Pregnancy Risk Group C.